Prevention of secondary caries by a new antibacterial compound - Ali Eskandarizadeh; Iman Mohammadzadeh; Arash Shahravan; Mohammad Bavafa; Sina Kakooei; Molouk Torabi (Wolters Kluwer Medknow Publications, 2020)
Background: Since secondary caries is one of the main problems of dental composites. The creation of an antibacterial property in these composites is essential. The objective of this study was to synthesize 3-(2, 5-dimethylfuran-3-yl)-1H-pyrazole-5(4H)-one and check its biocompatibility and antibacterial properties in flowable dental composites. Materials and Methods: In this animal study, the antibacterial activity of flowable resin composites containing 0-5 wt% 3-(2,5-dimethylfuran-3-yl)-1H-pyrazole-5(4H)-one was investigated by using agar diffusion and direct contact tests on the cured resins. Statistical analysis was performed using one-way ANOVA test (P < 0.001). Thirty male albino Wistar rats were used, weighing 200-250 g. Animals were randomly divided into three groups of ten; each animal received three implants, 3-(2, 5-dimethylfuran-3-yl)-1H-pyrazole-5(4H)-one, penicillin V, and an empty polyethylene tube. A pathologist, without knowing the type of material tested and the timing of the test, examined the samples. Statistical analysis was performed using Kruskal-Wallis test (P < 0.001). Results: According to our findings, although the agar diffusion test reveals no significant difference between the groups, the direct contact test demonstrates that, by increasing the 3-(2,5-dimethylfuran-3-yl)-1H-pyrazole-5(4H)-one content, the bacterial growth was significantly diminished and the 3-(2,5-dimethylfuran-3-yl)-1H-pyrazole-5(4H)-one has a good biocompatibility (P < 0.05). Conclusion: Incorporation of 3-(2,5-dimethylfuran-3-yl)-IH-pyrazole-5(4H)-one into flowable resin composites can be useful to prevent Streptococcus mutans activity.